Impact of trade cost, market size and foreign direct investment on export quality in trade between China and developing economies - Eshraghi, Mastooreh (2013)
Recently, the issue of the quality in international trade attracts many attentions of the researchers. In fast world economy, the patterns of trade are not only determined by the differences in technology and factor endowments of the countries but also additional determinant, such as quality has a significant effect on trade. The aim of this study is to investigate the role of the export quality in trade between China and developing economies. The first objective of this research is to measure the product quality improvement for trade between China and developing countries. Using bilateral trade relationships during 2000 to 2008, this study applies a method measuring the share of product quality in vertical and horizontal intra-industry trade to present evidence on product export quality. For China, intra-industry trade with South Africa is more profitable than the other selected countries. The percentage of high quality products related to South Africa is significantly high in both periods making China a high quality exporter. The highest positive growth of high quality products belongs to the Russian Federation. Thailand and Malaysia are in second and third place. These results suggest that China should involve more in trade relation with the Russian Federation, Thailand and Malaysia focusing more on improving their product quality rather than product quantity. The second objective of this study is to examine the effects of trade costs and market size on export quality. The gravity equation with multilateral resistance terms using the Heckman selection method is applied. The trade data are from 2005 to 2009 by the SITC 5-8. Results represent a significant positive relationship between market size of trade partners and export quality. There is also a significant positive relationship between trade costs and export quality showing the higher trade costs lead to more export of high quality products. Therefore, the policy of trade in China should be toward changing their quality trade’s partner to more distance countries resulting in gaining more benefit. The third objective of this study is to examine the relationships between FDI inflow and export quality. The ARDL approach is applied to estimate the long and short run effects of FDI on export quality. The data for total trade between China and the world in 1980-2010 are used. The FDI coefficients are significantly positive implying a complementary relationship between FDI and the export quality. China has focused on attracting FDI to increase their export. It is worth for China to concentrate more on export quality not only to developing countries but also to developed countries. There is also a positive relationship between the size of the economy and export quality. High population rate makes China a huge market that exports high quality goods since high rate of FDI creates an opportunity for China to improve their technology. The relationship between exchange rate and export quality is insignificantly positive. With recent instability in some currencies such as Euro and U.S. Dollar, exporting the high quality goods is more profitable for China.